Mechanism for efficient nitrogen utilization by peach rootstock GF677 (Prunus amygdalus × Prunus persica) in alkaline orchard soils - Song, Hai-yan; Zhao, Ke; Wang, Qiang; Jiang, Guo-liang; Sun, Shu-xia; Li, Jing; Tu, Mei-yan; Wang, Ling-li; He, Cheng-yong; Wang, Tie; Chen, Dong (Frontiers in Plant Science, 2025)
GF677 is a widely used peach rootstock with resistance to chlorosis and continuous-cropping disease. Peach varieties grafted onto GF677 generally exhibit larger leaf area and deep green foliage in alkaline soils, demonstrating a higher nitrogen utilization efficiency (NUE) than other rootstocks. To elucidate the mechanism for the higher NUE of GF677, we grafted four peach varieties onto either GF677 or peach (Prunus persica, the control rootstock) in alkaline soils. The results revealed that grafting of peach varieties onto GF677 resulted in larger leaf area and significantly higher total nitrogen content than grafting onto the control rootstock. Comparative transcriptomic analysis and WGCNA showed that the grafting onto GF677 significantly up-regulated 13 genes related to nitrogen uptake, transport, and reuse, while grafting onto the control rootstock up-regulated two monothiol glutaredoxin-encoding genes, in the leaves of different peach varieties. RT-qPCR further confirmed that four genes, including PpNRT1, PpNRT4, PpGLDH, and PpGRF9, may play crucial roles in the nitrogen utilization of GF677. Additionally, PpMGrx2 may play an important role in the response of peach (Prunus persica) to alkaline stress. This study elucidates the mechanism underlying the efficient nitrogen utilization of GF677, providing an important basis for the application and improvement of peach rootstock varieties.